Pemodelan dan Simulasi Path Planning Robot Mobil Menggunakan Metode Ant System Pada Lingkungan Terstruktur - Suhendri Suhendri; Nurita Evitarina; Rama Saktriawindarta (Fakultas Teknik Universitas Muhammadiyah Bengkulu, 2026)
Path planning is a fundamental problem in mobile robot navigation that requires efficient route optimization while avoiding obstacles. This study implements the Ant System method to solve the mobile robot path planning problem using a modeling and simulation approach in a structured environment. The path planning process utilizes pheromone mechanisms and heuristic information to determine an optimal path from the initial state to the goal state. A total of ten simulation experiments were conducted with variations in the number of intermediate coordinates, iterations, and ants. The results show that the proposed method successfully generated collision-free paths in all experiments, with path lengths ranging from 31.4915 to 32.6788 units. The analysis indicates that the balance between the number of intermediate coordinates, iterations, and ants significantly affects path quality, where well-balanced parameters produce smoother and more stable trajectories. Overall, the Ant System method achieved a 100% success rate, demonstrating its effectiveness and reliability for mobile robot path planning in structured environments.